Immunization strategies in advanced melanoma - Schadendorf, Dirk (Biogenic amines, 1999)
Provides information on a study about the effect of immunization on melanoma cells. Explanation on melanoma and tumor immunology; Rationale for cytokine gene transfer; Implication to vaccine design.
Gesehen am 21.02.2019